Identification Of Candida albicans in Oral Mucosal Swabs Of Smokers In The Gang Siswa Raya Kampung Sirnagalih Kota Tangerang - Fadillah, Muhammad Arief; Ratu Muawwadah; Ridwanulloh, Mohammad; Hamtini, Hamtini; Nurnida, Rossy (Journal of Medical Laboratory Research, 2024)
Candidiasis is a primary or secondary mycotic infection caused by members of the genus Candida and other genera, where Candida is one of the various forms of yeast. This study aims to determine the presence of Candida albicans fungus in oral mucosa swabs of smokers in the Gang Siswa Raya, Kampung Sirnagalih, Kota Tangerang based on smoking frequency and duration of smoking. This study uses a descriptive method, namely research with the aim of describing the presence of Candida albicans in oral mucosa swabs of smokers in the Gang Siswa Raya, Kampung Sirnagalih, Kota Tangerang using Sabouraud Dextrose Agar media and Germ tube tests. A total of 20 samples from 97 smokers data were collected. The results of the examination showed that there were fungi in the oral mucosa swab samples of smokers in the Gang Siswa Raya, Kampung Sirnagalih, Kota Tangerang as much as 40%. Then there is the growth of Candida albicans fungus in smokers with a smoking frequency of >3 years as much as 40%. Then there is the growth of Candida albicans fungus in smokers with a smoking frequency of >10 cigarettes a day as much as 35%.